Influence of Thermal Cycles Number on Bond Strength of Metallic Brackets to Ceramic - Jurubeba,José Eliú Pereira (2017)
Abstract The aim of this study was to evaluate the effect of different number of thermal cycles on the shear bond strength (SBS) of metallic orthodontic brackets bonded to feldspathic ceramic by a composite resin. Twenty-five ceramic cylinders were etched with 10% hydrofluoric acid for 60 s and received two layers of silane. Brackets were bonded to the cylinders using Transbond XT and assigned to 5 groups (n=5): Group 1 - Control group (without thermal cycling); Group 2 - 500 thermal cycles; Group 3 - 5,000 thermal cycles; Group 4 - 7,000 thermal cycles and Group 5 - 10,000 thermal cycles. Light-activation was carried out by Radii Plus LED. SBS testing was carried out after 24 h of storage in deionized water and thermal cycling (5/55 oC and 30 s dwell time). Five brackets were bonded to each cylinder, totalizing 25 brackets for each group. Data were submitted to one-way ANOVA and Tukey’s test (α=0.05). The Adhesive Remnant Index (ARI) was evaluated at 8× magnification. The SBS (MPa) of control group (9.3±0.8), 500 (9.0±0.7) and 5,000 (8.4±0.9) thermal cycles were significantly higher than those after 7,000 (6.8±0.6) and 10,000 (4.9±1.0) thermal cycles (p<0.05). The ARI showed a predominance of Scores 0 (adhesive failure) prevailed in all groups, as shown by the ARI, with increased scores 1 and 2 (mixed failures) for control group and 500 thermal cycles. In conclusion, thermal fatigue may compromise the bonding integration between metallic brackets and ceramic restorations. For in vitro testing, use of at least 7,000 cycles is advised to result in significant fatigue on the bonding interface.